Implementation Of Saumlaki Traditional Market Relocation Policy In Tanimbar Islands District - Bria, Yonivasius; Lumingkewas, Lexi; Mamonto, Fitri (Technium Social Sciences Journal, 2023)
The market is one of the important media that is widely used by the wider community in meeting their daily needs. A negative market image is often attached to the market because it creates many public problems in it. The existence of the market must be paid attention to in order to create a balanced regional and national economy. The market relocation program was initiated with the intention of answering existing problems by touching the physical condition of the market which was not feasible and increasing the income of traders for the welfare of the family economy and employment. The aim of this research was to determine the factors that influence the relocation policy of the traditional saumlaki market. The method used in this research is descriptive qualitative analysis. Qualitative descriptive method is used with the aim of providing an explanation in answering the formulation of the problem, namely the determinant factor in carrying out the implementation of public policies that traders state that the policy to relocate this market is good, it’s just that some traders also do not agree to be relocated because the location of the Omele Sifnana Market is far from the heart of Saumlaki City. And also the influence of the environmental conditions of the Tanimbar Islands District Government’s policy on the relocation of Saumlaki Market to Omele Sifnana Market including public policy environmental conditions, economic environmental conditions, socio-cultural environmental conditions and regional original income so that from environmental conditions this policy is expected to answer the challenges of the people’s economy, the government The area of the Tanimbar Islands Regency in formulating market relocation policies in order to create prosperity and employment for the people of the Tanimbar Islands Regency and outside communities.